Efeito do preparo do solo e resíduo da colheita de cana-de-açúcar sobre a emissão de CO2 - Moitinho, Mara Regina [UNESP]; Padovan, Milton Parron; Panosso, Alan Rodrigo [UNESP]; La Scala Jr, Newton [UNESP] (Sociedade Brasileira de Ciência do Solo, 2013)
The soil is one of the main C pools in terrestrial ecosystem, capable of storing significant C amounts. Therefore, understanding the factors that contribute to the loss of CO2 from agricultural soils is critical to determine strategies reducing emissions of this gas and help mitigate the greenhouse effect. The purpose of this study was to investigate the effect of soil tillage and sugarcane trash on CO2 emissions, temperature and soil moisture during sugarcane (re)planting, over a study period of 15 days. The following managements were evaluated: no-tillage with crop residues left on the soil surface (NTR); without tillage and without residue (NTNR) and tillage with no residue (TNR). The average soil CO2 emission (FCO2) was lowest in NTR (2.16 µmol m-2 s-1), compared to the managements NTNR (2.90 µmol m-2 s-1) and TNR (3.22 µmol m-2 s-1), indicating that the higher moisture and lower soil temperature variations observed in NTR were responsible for this decrease. During the study period, the lowest daily average FCO2 was recorded in NTR (1.28 µmol m-2 s-1), and the highest in TNR (6.08 µmol m-2 s-1), after rainfall. A loss of soil CO2 was lowest from the management NTR (367 kg ha-1 of CO2-C) and differing significantly (p<0.05) from the managements NTNR (502 kg ha-1 of CO2-C) and TNR (535 kg ha-1 of CO2-C). Soil moisture was the variable that differed most managements and was positively correlated (r = 0.55, p<0.05) with the temporal variations of CO2 emission from NTR and TNR. In addition, the soil temperature differed (p<0.05) only in management NTR (24 °C) compared to NTNR (26 °C) and TNR (26.5 °C), suggesting that under the conditions of this study, sugarcane trash left on the surface induced an average rise in the of soil temperature of 2 ºC.

O solo é um dos principais compartimentos de carbono no ecossistema terrestre, capaz de armazenar quantidades expressivas desse elemento e, portanto, a compreensão dos fatores que contribuem para as perdas de CO2 em solos agrícolas é fundamental para determinar estratégias de redução das emissões desse gás e ajudar a mitigar o efeito estufa. O objetivo deste estudo foi investigar o efeito do preparo do solo e da deposição de resíduos da cultura da cana-de-açúcar na emissão de CO2, temperatura e umidade do solo, durante a reforma do canavial, ao longo de um período de 15 dias. Os manejos avaliados foram: sem preparo do solo e mantendo os resíduos da colheita sobre a superfície do solo (SPCR); sem preparo do solo e sem resíduo (SPSR) e com preparo do solo e sem resíduo (CPSR). A menor média de emissão de CO2 do solo (FCO2) foi observada no manejo SPCR (2,16 µmol m-2 s-1), quando comparado aos manejos SPSR (2,90 µmol m-2 s-1) e CPSR (3,22 µmol m-2 s-1), indicando que as maiores umidades e menores variações da temperatura do solo, observadas em SPCR, foram os fatores responsáveis por tal diminuição. Durante o período de estudo, a menor média diária da FCO2 foi registrada em SPCR (1,28 µmol m-2 s-1) e a maior em CPSR (6,08 µmol m-2 s-1), após a ocorrência de chuvas. A menor perda de C-CO2 do solo foi observada no manejo SPCR (367 kg ha-1 de C-CO2), diferindo significativamente (p<0,05) dos manejos: SPSR (502 kg ha-1 de C-CO2) e CPSR (535 kg ha-1 de C-CO2). A umidade do solo foi a variável que apresentou valores mais diferenciados entre os manejos, sendo positivamente correlacionada (r = 0,55; p<0,05) com as variações temporais da emissão de CO2 nos manejos SPCR e CPSR. Em adição, a temperatura do solo diferiu (p<0,05) somente no manejo SPCR (24 ºC), quando comparada aos manejos SPSR (26 ºC) e CPSR (26,5 ºC), sugerindo que, para as condições deste estudo, o resíduo da cana-de-açúcar retido sobre a superfície propiciou uma temperatura do solo, em média, 2 ºC mais amena.
Effect of soil tillage and sugarcane trash on CO2 emission
Keywords: respiração do solo; manejo da cana-de-açúcar; temperatura e umidade do solo; soil respiration; sugarcane management; soil temperature and moisture